The Effectiveness Of Assure Model Using The Listening TeamMethod In Increasing Learning Motivation On Tajwid Law Material - Teti Nurhalizah; Nurhakim, Riki Rahman; Latuconsinah, Zainal Abidin; Ruswandi, Uus (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
This study aims to explore the effectiveness of the ASSURE learning modelin increasing student motivation in the subject matter of tajwid law. Thisresearch is important to be researched to provide knowledge to all educators or readers about a learning model and method that can encourage the growthof student motivation in studying PAI. This study uses a qualitativeapproach and an analytic descriptive method. Data collection techniquesinclude observation to explore the learning process, interviews to obtain dataon student learning characteristics and teacher teaching methods, anddocumentation to find relevant data according to research. The researchsubjects were students and teachers of PAI subjects. The results showed thatthe use of the ASSURE learning model for Tamansiswa Rancaekek HighSchool students with the listening team method was able to increase studentlearning motivation, which can be seen from the students' activeness inanswering questions, the suitability of answers to questions, and providingexplanations based on what students have understood